Enhancement of postharvest life of dendrobium flower - Jomy TG (Department of Horticulture, College of Agriculture, 1997)
A study was conducted at the Department of Horticulture, College of Agriculture, Vellayani from September 1996 to January 1997 to find the effects of various postharvest chemical treatments in improving quality and vase life of Dendrobium cut-flowers and to identify the best combination of chemicals for maximising vase life. The study comprised of four experiments. All of them were laid out in Completely Randomised Design except the fourth which was in factorial CRD. The conditioning treatments, pulsing and use of holding solutions were significantly influence the vase life of Dendrobium varieties. The best conditioning treatments observed in Expt.l were tap water altered to pH 3.0 (T 4) and 3.5 (T 3) which recorded a vase life of 20.67 days and 19.67 days respectively. Changes in the fresh weight, dry weight, water content, sugar content and flower size during vase life period were not influenced by the conditioning treatments. Irrespective of the treatments the fresh weight of the inflorescences increased upto the fourth day and by the seventh day a decline proceeded upto the cessation of vase life. So also the flowers were found to maintain their maximum length and width upto the seventh day of the vase life period. In experiment 2, pulsing with a combination of 4% sucrose and 400 ppm 8-HQ for six hours was found